Evaluasi Mutu Beras dengan Kesesuaian Good Handling Practices dan Good Manufacturing Practices di Kabupaten Bogor - Dwi Zuwarman; Sutrisno Suro Mardjan; Rokhani Hasbullah (Jurnal Keteknikan Pertanian, 2020)
Milled rice is one of the most important agricultural commodities for Indonesian people as staple food. Consumers tend to not know how to differentiate good or low quality of rice. Rice mill (RMU) in Bogor Regency mostly do not have quality standard comply with Indonesian National Standard (SNI). The purpose of this study was to identify the quality of rice and milled rice produced by RMU in Bogor Regency and evaluate the suitability of the application of rice and milled rice handling in RMU to Good Handling Practices (GHP) and Good Manufacturing Practices (GMP). The parameters measured were analysis of rice and milled rice quality and data analysis. The data resulted from measuring the quality of grain and rice was obtained from interview and observation. The results showed that four RMU rice samples not included in the class category SNI 6128: 2015 and two samples included in Medium III (M-3). On the postharvest handling conformity level was 44.92 percent for GHP and 60.25 percent for GMP. GHP and GMP guidelines were not yet fully applied by rice milling unit (RMU).